L-Tyrosine administration modulates the effect of transcranial direct current stimulation on working memory in healthy humans. (May 2017) - Jongkees, Bryant J.; Sellaro, Roberta; Beste, Christian; Nitsche, Michael A.; Kühn, Simone; Colzato, Lorenza S.
Abstract: Background: Transcranial direct current stimulation (tDCS) is an increasingly popular method of modulating cognitive functions in humans. However, some doubt its efficacy as findings are inconsistent or remain unreplicated. It is speculated dopamine (DA) might play an important role in this inconsistency, by determining the direction and strength of the cognitive-behavioral effects of tDCS. However, so far evidence for this hypothesis has been correlational in nature, precluding definitive conclusions. Objective: The present proof-of-principle study aimed at investigating a potentially causal role for DA in the effect of tDCS on cognition in healthy humans. Methods: In Experiment 1 we aimed to replicate previous findings showing administration of DA's precursorl -Tyrosine (Tyr), presumably by inducing a modest increase in DA level, can enhance working memory (WM) performance as assessed with a verbal N -back task. In Experiment 2 we investigated the effect of Tyr administration on bilateral tDCS over dorsolateral prefrontal cortex (DLPFC) and WM. Results: Experiment 1 showed Tyr administration enhances performance in a verbal N -back task. Experiment 2 showed Tyr modulates the effect of bilateral tDCS over DLPFC on WM. Specifically, tDCS had opposite effects on performance depending on current direction through the brain and Tyr administration. Conclusions: The present study provides two major findings. First, we replicate Tyr's beneficial effect on verbal WM. Second, our results indicate a causal role for DA in the effect of tDCS on cognition. For this reason, we encourage future studies to consider the modulating effect of DA, as a step towards more consistent and replicable results regarding the efficacy of tDCS.